Synthesis of pyrrolidine-based analogues of 2-acetamidosugars as N-acetyl-d-glucosaminidase inhibitors. (29th May 2015) - Tran, Anh Tuan; Luo, Bo; Jagadeesh, Yerri; Auberger, Nicolas; Désiré, Jérôme; Nakagawa, Shinpei; Kato, Atsushi; Zhang, Yongmin; Blériot, Yves; Sollogoub, Matthieu
Abstract: A ring-contraction strategy applied to β-azido, γ-hydroxyazepanes yielded after functional group manipulation new tetrahydroxylated pyrrolidines displaying an acetamido moiety, one of these iminosugars demonstrating low micromolar inhibition on N-acetylglucosaminidases. Graphical abstract: Highlights: A new family of amino-functionalised pyrolidines was synthesized. A ring-contraction of β-azido, γ-hydroxyazepanes was used. A low micromolar inhibitor of β-N-acetylehexosaminidase identified.